President’s Message - Vandale, Tanya (Operating Room Nurses Association of Canada Journal, 2024)
Welcome back! On behalf of the ORNAC board of directors, I’m excited to announce the relaunch of the ORNAC Journal! After nearly two years on hold, we’re back, and one of the most significant changes is our transition to an open access publication. This move ensures that perioperative nursing research and knowledge are accessible to everyone.